Erythroid Krüppel-like factor (EKLF) contains a multifunctional transcriptional activation domain important for inter- and intramolecular interactions. - Chen, X (1996)
Erythroid Krüppel-like factor (EKLF) is a red cell-restricted transcriptional activator that plays a dominant role in establishing high levels of beta-globin gene expression during erythroid ontogeny. Although its DNA binding domain belongs to the well-studied class of Krüppel-like zinc fingers, its proline-rich activation region has not been thoroughly examined. We have analyzed this region by monitoring the functional effects of its mutagenesis upon EKLF activity in vivo and in vitro. First, using co-transfection assays, we find that the transactivation region contains discrete stimulatory and inhibitory subdomains. Second, in vitro binding assays indicate that the inhibitory domain exerts its effect in cis by interfering with DNA binding. Third, in vivo competition assays demonstrate that EKLF interacts with a positive-acting cellular factor, and that the domain responsible for this trans interaction lies within a 40 amino acid sequence that is coincident with the EKLF minimal transactivation domain. Finally, site-directed mutagenesis of this domain implies that conformation and/or phosphorylation status of its central core may be critical for such interactions. These results point towards post-translational steric and/or allosteric control of EKLF function that may be important not just for its DNA binding ability, but also for its potential to interact with other proteins that fully establish the correct stereospecific array leading to efficient switching of beta-globin transcription during development.